Bangladesh Policy Research and Strategy Support Program (BPRSSP) - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
The Bangladesh Policy Research and Strategy Support Program (PRSSP) for Food Security and Agricultural Development, funded by the United States Agency for International Development (USAID), is the largest project IFPRI has ever had in Bangladesh. Building on previous work in the country alongside government partners in the Ministry of Food and Disaster Management and the Ministry of Agriculture, IFPRI launched the program in October 2010. PRSSP fills the need for demand-driven food and agriculture research in response to Bangladesh’s country investment plan for agriculture, food security, and nutrition. It aims to generate information on critical issues, strengthen analytical capacity within the country, and stimulate policy dialogue. Its main objectives are to provide policy options and advisory services, collaborate with national institutions to evaluate and explain evidence, and find effective ways to deliver options and evidence to decision makers and stakeholders.